Two new species of the coffinfish genus Chaunax (Lophiiformes: Chaunacidae) from the Indian Ocean - Ho, Hsuan-Ching; Last, Peter R. (Zootaxa, 2013)
Two new coffinfishes, Chaunax nebulosus n. sp. and Chaunax africanus n. sp., are described from the Indian Ocean. Both species belong to the C. fimbriatus-species group which is characterised by having filaments on the dorsal head and a complex color pattern on the dorsal surface. They are morphometrically and meristically conservative but differ in coloration. Chaunax nebulosus can be distinguished from its closest relatives by its dense covering of very small, irregular grayish green spots and having 5 small blackish markings on its dorsal surface. Chaunax africanus can be distinguished from other members  in having a colour pattern of long narrow brown bars on the dorsal-fin base and head (forming a radiate pattern around the eye), and a complex white reticulate pattern (often double-lined) over the entire dorsal surface. Comments on species occurring in Indian Ocean and the status of members of C. fimbriatus-species group are also provided.